Patterns of growth and partitioning of fat depots in tropical fat-tailed Menz and Horro sheep breeds - Negussie, E.; Rottmann, O.J.; Pirchner, F.; Rege, J.E.O. (Elsevier, 2003)
A total of 147 Menz and Horro lambs of both sexes were serially slaughtered and dissected at five different stages of growth to define the pattern of growth and partitioning of fat among body depots in indigenous Ethiopian Menz and Horro sheep breeds. The GLM procedure of SAS and allometric growth equation were used to assess the effects of various factors on the growth of body depots and to estimate its growth relative to total carcass fat (TCF) and empty body weight (EBW), respectively. Results obtained showed that the growth of carcass fat (CF), non-carcass fat (NCF) and tail fat (TF) is significantly affected by the genotype (P<0.001) and stages of growth (P<0.001) of lambs. Except for CF, the growth of both NCF and TF were also significantly affected (P<0.001 and P<0.05) by the sex and the season in which the lambs were born. Of the two breeds, the Menz sheep deposited more fat into the carcass and less into the non-carcass depots as compared to the Horro sheep and ewe lambs in both breeds deposited more fat intra-abdominally than the ram lambs. The highest allometric growth coefficient was obtained for TF (1.2–2.1 relatively to TCF and EBW) and the lowest for NCF (0.8–1.3 relative to TCF and EBW) indicating that the former is a late developing while the later is an early maturing depot in the tropical fat-tailed Menz and Horro sheep breeds.